Vegetation Analysis and Tree Architecture Model at the Kupang State Agricultural Polytechnic Arboretum - Nababan, Badia Roy Ricardo; Nufus, Mitha Rabhiyatul; Takoy, Darmawana (Jurnal Biologi Tropis, 2025)
The Kupang State Agricultural Polytechnic Arboretum is a vegetation collection located in an area with arid and semi-arid climate characteristics. Understanding the vegetation composition and tree architecture model is important information for effective arboretum management and conservation planning in the East Nusa Tenggara region. This study aims to analyze the vegetation composition to determine the Importance Value Index (IVI) at various growth phases and to identify the dominant tree architecture models in the Kupang State Agricultural Polytechnic Arboretum.Vegetation data collection was conducted using the line transect method, covering the seedling to tree phases. The data were analyzed using INP calculations, while tree architecture models were analyzed descriptively and exploratively based on tropical tree architecture references. The results of the vegetation analysis showed that dominant species such as Kirinyuh (Chromolaena adorata), Gewang (Corypha utan), Gamal (Gliricidia sepium), and Jati Putih (Gmelina arborea) had the highest importance values in each growth phase, indicating high adaptability to dry land conditions. The most commonly found tree architecture model was the Troll Model (in 9 of 12 species), characterized by a broad and leafy canopy. The Attims and Rauh models were also found in several species with specific ecological functions. The dominance of adaptive species and the Troll Model indicate that the arboretum functions optimally as shade, windbreak, and erosion control, which are essential for ecological functions in drylands. This study provides important ecological baseline data for conservation management and sustainable green open space development in the semi-arid region of East Nusa Tenggara.